Cross-Cultural Communication: Interactions Based on Developing Culture (KULT_online, 2012)
Since the reform and opening-up policy of 1978, great changes have occurred in China: not only Chinese society changed, but also ideas, values, and behaviours of Chinese people. This results in changes of traditional Chinese values in cross-cultural communication. Against this background, the developing trend of communication between Chinese and Germans is the main question of LIU Yue's book "Kulturspezifisches" Kommunikationsverhalten? Eine empirische Untersuchung zu aktuellen Tendenzen in chinesisch-deutschen Begegnungen ('Culturally Specific' Communication Behaviour? An Empirical Study on Current Tendencies in Chinese-German Encounters). Through analysing current intercultural communication phenomena, she finds out the existing problems, such as misunderstandings between Chinese and Germans, and brings forward some methods for improvement, which contribute to successful cross-cultural communication between China and Germany, for example integrating cultural awarenness into foreign language teaching.